Transformasi Sosial Budaya Petani Edamame: dari Tradisional ke Modern - Musyarofah; Anindya Fajarini (Entita: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2025)
Social and Cultural Changes in Farming Communities Modernization will certainly have an impact, where farmers who previously only knew the traditional system then prefer to implement the new system offered by the company. This study aims to determine the socio-cultural changes in the farming community in Panti Village, Jember Regency and utilize it as contextual teaching materials for social studies subjects. This study uses a qualitative approach with a naturalistic phenomenology method. Data collection techniques used in this study are non-participant observation, interviews, semi-structured and unstructured data and documentation techniques. Data analysis uses an interactive analysis model developed by Miles and Huberman. Data validity is carried out through triangulation of data sources and methods. The results of the study indicate that the socio-cultural changes in the edamame farming community in Panti, especially changes in the economic system related to livelihoods; community lifestyle; social interaction especially from the participation of residents/edamame farmers in social and religious activities; changes in socio-economic structures include patterns of relationships/partnerships between landowners and edamame companies in Jember.